Dynamic Optical Amplifiers Enable Distributed Equalization in Optical Transmission Systems - Hongqiang Zou; Da Liu; Kai Zhang (IEEE Photonics Journal)
In this paper, we design and simulated a novel dynamic gain flattening filter (DGFF) module based on polarization-insensitive liquid crystal on silicon (PI-LCoS). The DGFF module measures 26*10.5 mm in size and integrates four DGFFs. Its compact design and minimal optical components reduce costs and enhance manufacturability. In our lab, we built a 6THz C-band transmission system and compared a novel distributed equalization scheme using DGFF in EDFAs with traditional centralized schemes. Results showed that this scheme effectively balanced OSNR across channels, reducing OSNR flatness from 3.5 dB to 0.5 dB. Additionally, it decreased ROADM station attenuation, leading to an average OSNR improvement of about 0.47 dB.